THE RIPPLE EFFECT: MOTIVATIONS AND DISRUPTIONS IN ONLINE WORD-OF-MOUTH EXCHANGES - Thompson, Emily Grace; Lee, Daniel Joseph (Ayden Journal of Management and Social Sciences, 2024)
As e-commerce continues to thrive, electronic wordof-mouth (eWoM) has emerged as a pivotal source of information for online consumers. EWoM encompasses informal online communications concerning goods, services, or sellers, significantly influencing consumer purchasing decisions. This study delves into the factors motivating online consumers to contribute eWoM content, applying the expectancy disconfirmation theory (EDT) to explore the role of disconfirmation and satisfaction in shaping their intentions. We investigate which types of eWoM content are most affected by these perceptions and feelings, using data collected from online consumers who have booked hotels through online travel agents. Our findings offer valuable insights into eWoM engagement and provide practical recommendations for marketers aiming to encourage word-of-mouth participation. In an era where usergenerated content holds immense sway, understanding the dynamics of eWoM is crucial for businesses seeking to thrive in the digital marketplace